Investigating waste separation at source behaviour among South African households: the case of Abaqulusi Local Municipality. Issue 4 (2nd October 2022) - Roos, Claudine; Baron, Christiaan; Cilliers, Dirk; Alberts, Reece; Retief, Francois; Moolman, Jurie
ABSTRACT: This study aimed to investigate waste separation at source behaviour among South African households in Abaqulusi Local Municipality in KwaZulu-Natal. Behaviour in this context refers to determining current waste separation practices, and the willingness of households to participate in waste separation in future. Awareness and attitudes towards source separation, as well as certain socio-demographic variables were determined. Door-to-door surveys, supported by structured questionnaires, were used to collect data from 757 households. Only 16% households reported current participation in waste separation practices. Less than one-third of the households indicated that they would be willing to participate in waste separation practices in the future. Gender (p = 0.02, V = 0.04) and income (p = 0.01, V = 0.15) had a statistically significant relationship with waste separation practice, but were of low practical significance, whereas household size (p = 0.06, V = 0.1) was both statistically and practically insignificant. When considering these variables and their relationship with willingness to participate in separation at source in future, gender (p = 0.003, V = 0.1), household size (p = 0.01, V = 0.3) and income (p = 0.01, V = 0.28) had a statistically significant relationship with willingness, with a low to moderate practical significance.